MANFAAT PEMBERDAYAAN AIR TANAH BAGI PETANI HORTIKULTURA DI KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - Sukarno, .; Sompie, Bonny F. (JURNAL ILMIAH MEDIA ENGINEERING, 2014)
Research on groundwater for various purposes, i.e. for drinking water, for agriculture water, hotels water, industrial water, or water for needs of the city has been investigated by many researchers, until nowadays it's been a lot of countries that have successfully empower groundwater, such as the State of Japan in the city of Kumamoto. Groundwater research in this paper was conducted in the Kecamatan Modoinding with the objective to investigate the potential of groundwater for horticultural crops. Implementation research shows that the average climate data, which includes temperatureÂ  27.60C, air humidity was about 99.83%, evaporation was about 2.19mm, wind speed was about 4.46km/day, the sun shines was about 40.13% and an average rainfall depth of 206.6mm, the existence of two mountains, four streams that are intermittent and perennial characteristics, two lakes and groundwater wells located within the study location, all the indicators are variables and parameters that can be used to determine the groundwater potential of the fields. The results show there is a potential of groundwater in the Kecamatan Modoinding with relatively large volume can be used for vegetable crops in the summer, however more research needs to be done to empower the groundwater at a low cost. Key words: Groundwater potential, exploration and exploitation, horticultural crops.